Integrative preimplantation genetic testing analysis for a Chinese family with hereditary spherocytosis caused by a novel splicing variant of SPTB - Tian, Yafei; Wang, Yao; Yang, Jingmin; Gao, Pengfei; Xu, Hui; Wu, Yiming; Li, Mengru; Chen, Hongyan; Lu, Daru; Yan, Hongli (Frontiers in Genetics, 2023)
Hereditary spherocytosis (HS), the most common inherited hemolytic anemia disorder, is characterized by osmotically fragile microspherocytic red cells with a reduced surface area on the peripheral blood smear. Pathogenic variants in five erythrocyte membrane structure-related genes ANK1 (Spherocytosis, type 1; MIM#182900), SPTB (Spherocytosis, type 2; MIM#616649), SPTA1 (Spherocytosis, type 3; MIM#270970), SLC4A1 (Spherocytosis, type 4; MIM#612653) and EPB42 (Spherocytosis, type 5; MIM#612690) have been confirmed to be related to HS. There have been many studies on the pathogenic variants and mechanisms of HS, however, studies on how to manage the transmission of HS to the next generation have not been reported. In this study, we recruited a patient with HS. Targeted next-generation sequencing with a panel of 208 genes related to blood system diseases detected a novel heterozygous variant in the SPTB: c.300+2dup in the proband. Sanger sequencing of variant alleles and haplotype linkage analysis of single nucleotide polymorphism (SNP) based on next-generation sequencing were performed simultaneously. Five embryos were identified with one heterozygous and four ﻿not carrying the SPTB variant. Single-cell amplification and whole genome sequencing showed that three embryos had varying degrees of trisomy mosaicism. One of two normal embryos was transferred to the proband. Ultimately, a healthy boy was born, confirmed by noninvasive prenatal testing for monogenic conditions (NIPT-M) to be disease-free. This confirmed our successful application of PGT in preventing transmission of the ﻿pathogenic variant allele in the HS family.